Selection of a representative core collection from the chilean common bean germplasm - Paredes, M; Becerra Velásquez, Viviana L.; Tay Urbina, Juan; Blair, Matthew W.; Bascur, G (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2010)
Race Chile is an important component of the genetic structure of the common bean (Phaseolus vulgaris L.). The germplasm bank of the Instituto de Investigaciones Agropecuarias INIA contains 1200 accessions distributed mainly into two Active Working Germplasm Banks at INIA La Platina (Santiago) and at INIA Quilamapu (Chillán) and also the Germplasm Base Bank at INIA Intihuasi (La Serena). The Chilean collection possesses accessions collected throughout the country. One way to study and use the germplasm stored at the Seed Banks is the formation of a core collection. The objectives of this work were: a) To establish a common bean core collection with the germplasm collected throughout the country, and b) to evaluate its representatives based on phenotypic data and to compare with data from the whole collection. The results indicated that the Chilean base collection contained accessions belonging to the Andean and Mesoamerican gene pools and to genotypes belong to race Chile, Perú, Nueva Granada, Mesoamérica and Durango. The Chilean bean core collection consisted of 246 accessions. Comparison for several phenotypic traits data from 246 accessions from the whole and core collection indicated the genetic variation expressed for each trait in the whole collection was quite well represented in the core collection. This core collection will be very useful for further phenotypic and genetic characterization and to select accessions for the bean breeding program.